Risk Assessment of Crisis Management in Response to Natural Disasters with an Emphasis on Earthquakes - Seyed Mojtaba Hosseini; Fatemeh Dirakvand; Omidreza Safarian; Ali Ayoubian (Civil Engineering Journal, 2019)
The aim of this study was to explain the risks of the crisis management process in responding to natural disasters with the focus on earthquakes. This quantitative, descriptive, analytic study was conducted in Doroud City, Lorestan province, Iran in 2017. The society of the research comprises all members of the Doroud Crisis Management team, out of which 140 people were selected by stratified random sampling. In order to collect data, self-made questionnaires comprising 40 questions and 6 domains (structural, therapeutic, help and rescue, safety, hygiene, logistics)and based on the Likert Five Option Spectrum (extremely low=1, extremely high=5)were used. To ensure the validity of the questionnaires, they were assessed and verified by experts in the field. To assess the reliability, however, the Cronbach's Alpha Coefficient of 0.89 was applied. The data was analyzed by mean, standard deviation, and Independent T-test and variance analysis using SPSS21. The findings showed that safety with a mean and standard deviation of 4.91±0.68 was the highest and structure with a mean and standard deviation of 2.03±0.64 was the lowest domains under the assessment of crisis management. Also, training courses in therapeutic and hygiene domains, and work experience in therapeutic, help and rescue, security, logistics domains made a considerable difference (p=0.05). From the perspective of the sample under study, the domains of therapeutic and hygiene have the highest importance factor, logistics was allocated the lowest priority. Applying the proper assessment of different risk frameworks, the researchers reviewed each domain proportionate to the probability of an earthquake in the study area. This way by identifying the potential hazards and risks in view of important and effective domains, the dangers could be prioritized and management programs could be implemented.